2003
DOI: 10.1051/forest:2003030
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological and climatic responses of Pinus elliottii var. densa in mesic pine flatwoods Florida, USA

Abstract: -Pinus elliottii Engelm. var. densa Little & Dorman is the only native sub-tropical pine in the US and is now restricted to an estimated 4.5% of its original area. To understand how this species might respond to changing environments, we examine the relationship between two hydrologic variables and growth of three stands of P. elliottii var. densa occurring along a hydrologic gradient using tree-ring records. The two variables were a short-term indicator of water status, precipitation minus potential evapotran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…This corroborates the findings of Ford and Brooks (2003), who found slash pine at its northern range limit in central Florida to be sensitive to water availability during times of high demand. RFA indicated that previous November and current September temperature and current September precipitation are the most important predictors of radial growth at NBP.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This corroborates the findings of Ford and Brooks (2003), who found slash pine at its northern range limit in central Florida to be sensitive to water availability during times of high demand. RFA indicated that previous November and current September temperature and current September precipitation are the most important predictors of radial growth at NBP.…”
Section: Discussionsupporting
confidence: 81%
“…Additionally, Ford and Brooks (2003) used tree-ring analyses on slash pine to examine the relationship between radial growth, precipitation minus potential evapotranspiration (P-PET, indicating water availability during times of high demand), and runoff (R, indicating access to groundwater) along a hydrologic gradient at Myakka River State Park. The oldest individual pine established in 1888, but most individuals established in the early decades of active fire suppression (ca.…”
Section: Previous Research On South Florida Slash Pinementioning
confidence: 99%
“…Other studies have shown that radial growth is related to both the previous and current year climate (e.g. Cook et al ., ; Ford & Brooks, ; García‐Suárez et al ., ; Harley et al ., ). In our study, radial growth of both functional groups responded to previous and current growing season number of storms, number of small storms, DSL, and AET/ P .…”
Section: Discussionmentioning
confidence: 97%
“…7a). Other studies have shown that growth of slash pine stands is positively correlated with water balance during the current growing season (Ford and Brooks 2003) and aboveground NPP in a longleaf pinewiregrass ecosystem was also positively correlated with seasonal water availability (Mitchell et al 1999). NPP, although highly variable, was also positively related to growing season precipitation, changing by .4 Mg C/ha over 600 mm range (r 2 ¼ 0.52, F ¼ 13.14, P , 0.05; Fig.…”
Section: Interannual Variability After Canopy Closurementioning
confidence: 97%